Improved imaging of Cochlear nerve hypoplasia using a 3‐tesla variable flip‐angle turbo spin‐echo sequence and a 7‐cm surface coil. (31st July 2013) - Giesemann, Anja M.; Raab, Peter; Lyutenski, Stefan; Dettmer, Sabine; Bültmann, Eva; Frömke, Cornelia; Lenarz, Thomas; Lanfermann, Heinrich; Goetz, Friedrich
<x xml:space="preserve">Abstract</x> Objective/Hypothesis Magnetic resonance imaging of the temporal bone has an important role in decision making with regard to cochlea implantation, especially in children with cochlear nerve deficiency. The purpose of this study was to evaluate the usefulness of the combination of an advanced high‐resolution T2‐weighted sequence with a surface coil in a 3‐Tesla magnetic resonance imaging scanner in cases of suspected cochlear nerve aplasia. Study Design Prospective study. Methods Seven patients with cochlear nerve hypoplasia or aplasia were prospectively examined using a high‐resolution three‐dimensional variable flip‐angle turbo spin‐echo sequence using a surface coil, and the images were compared with the same sequence in standard resolution using a standard head coil. Three neuroradiologists evaluated the magnetic resonance images independently, rating the visibility of the nerves in diagnosing hypoplasia or aplasia. Results Eight ears in seven patients with hypoplasia or aplasia of the cochlear nerve were examined. The average age was 2.7 years (range, 9 months–5 years). Seven ears had accompanying malformations. The inter‐rater reliability in diagnosing hypoplasia or aplasia was greater using the high‐resolution three‐dimensional variable flip‐angle turbo spin‐echo sequence (fixed‐marginal kappa: 0.64) than with the same sequence in lower resolution (fixed‐marginal kappa: 0.06). Conclusions Examining cases of suspected cochlear nerve aplasia using the high‐resolution three‐dimensional variable flip‐angle turbo spin‐echo sequence in combination with a surface coil shows significant improvement over standard methods. Level of Evidence NA. Laryngoscope, 124:751–754, 2014